‘미적 판단’에 주목하는 인문적 예술교육의 접근을 위한 일고찰－‘정치적’인 것과 ‘인문적’인 것의 개념적 관련성을 중심으로 - 최진 (교양교육연구, 11(2), 2017)
이 글은 현재 교육 현장에서 ‘인문적 소양’을 함양해야한다는 요구가 증가하고 있음에 주목하고 우선적으로 인문적 소양으로 제시될 수 있는 능력에 대한 개념적 명료화가 필요하다는 문제의식에서 출발한다. 필자는 그 능력이 ‘판단’ 능력이라고 가정하면서 이 제안을 철학적으로 정당화하기 위해 칸트가 자신의 제3비판서에서 다룬 ‘반성적 판단’으로서의 ‘미적 판단’의 개념에 주목한다. 이것은 규정적 판단과 달리 특정한 진리나 규범에 쉽게 종속되지 않는 ‘개별적’이고 ‘특수한’ 사안의 판정 능력을 의미한다는 점에서 우리의 주체적인 가치평가 능력과 관련된다. 미적 판단은 우리의 주관적인 감정에 호소하면서도 타인과 소통될 수 있는 보편적인 특성을 가지고 있는데, 이 글에서는 한나 아렌트가 칸트가 말하는 미적 판단의 속성에 토대하여 인간사에 관한 판단 능력을 설명하는 것을 주요한 논의 대상으로 삼는다. 특히 칸트가 해석한 ‘공통감각’ 및 ‘확장된 사유방식’이라는 개념을 아렌트가 자신의 방식으로 독특하게 이해한 것에 터하여, 인문적 소양으로서의 판단 능력은 ‘수단-목적’의 관계로 환원되지 않는 인간의 다양한 존재 방식을 바라볼 줄 아는 능력과 관련된다고 논증할 것이다. 이때 해석되는 인문성은 문화 및 예술을 통해 세계가 지속될 수 있는 세계성 및 인간들 ‘사이’의 공적 영역의 창출과 관련됨으로써 정치적인 것과도 개념적 관련성을 가질 수 있으며, 이것은 도덕교육보다는 예술교육의 접근에서 더 적절할 수 있다는 것을 보일 것이다. This study focuses on the awareness of a conceptual clarification of the ability to present humanistic qualities with the basis of an increasing demand for ‘humanistic qualities’ in the current educational field. The author notes the concept of ‘aesthetic judgment’ as ‘reflective judgment’ from Kant’s third Critique in order to philosophically justify this proposition while assuming the ability as the ability of ‘judgment’. This is in relation to the subjective value-assessment ability which means that the ability to judge ‘individual’ and ‘special’ matters are not easily subordinated to certain degree of truths or norms. ‘Aesthetic judgment’ appeals to our subjective emotions and has a universal characteristic that communicates with others. Therefore, this study’s main argument emphasizes Hannah Arendt’s explanation of Kant’s assertion that the ability to judge human affairs on the foundation of aesthetic judgment. In particular, Arendt’s unique understanding of the notion of ‘common sense’ and ‘enlarged mentality’ interpreted by Kant will be discussed to prove that the ability to recognize the various aspects of human are not reduced to the relation of ‘means - ends’ as humanistic qualities. The interpretation of humanity is associated with the creation of ‘public realm’ in-between worldliness and humans that can sustain the world through culture and art, thus this can be conceptually related to the political world and can produce an easier approach to art education than ethical education. KCI Citation Count: 5